Chest physiotherapy on intracranial pressure of critically ill patients admitted to the intensive care unit: a systematic review - Ferreira, Lucas Lima (Associação Brasileira de Medicina intensiva, 2013)
OBJECTIVE: To analyze the outcomes of increased or decreased intracranial pressure and/or the decrease in cerebral perfusion pressure resulting from respiratory physiotherapy on critically ill patients admitted to the intensive care unit. METHODS: Through a systematic review of the literature, clinical trials published between 2002 and 2012 were selected. The search involved the LILACS, SciELO, MedLine and PEDro databases using the keywords "physical therapy", "physiotherapy", "respiratory therapy" and "randomized controlled trials" combined with the keyword "intracranial pressure". RESULTS: In total, five studies, including a total of 164 patients between 25 and 65 years of age, reporting that respiratory physiotherapy maneuvers significantly increased intracranial pressure without changing the cerebral perfusion pressure were included. The articles addressed several techniques including vibration, vibrocompression, tapping, postural drainage, and the endotracheal aspiration maneuver. All patients required invasive mechanical ventilation. CONCLUSION: Respiratory physiotherapy leads to increased intracranial pressure. Studies suggest that there are no short-term hemodynamic or respiratory repercussions or changes in the cerebral perfusion pressure. However, none of the studies evaluated the clinical outcomes or ensured the safety of the maneuvers.